199k views
1 vote
2a + 3b + 5a - 4b + 2g

1 Answer

2 votes

5a+2 =2 (4+a)

Simplifying

5a + 2 = 2(4 + a)

Reorder the terms:

2 + 5a = 2(4 + a)

2 + 5a = (4 * 2 + a * 2)

2 + 5a = (8 + 2a)

Solving

2 + 5a = 8 + 2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2a' to each side of the equation.

2 + 5a + -2a = 8 + 2a + -2a

Combine like terms: 5a + -2a = 3a

2 + 3a = 8 + 2a + -2a

Combine like terms: 2a + -2a = 0

2 + 3a = 8 + 0

2 + 3a = 8

Add '-2' to each side of the equation.

2 + -2 + 3a = 8 + -2

Combine like terms: 2 + -2 = 0

0 + 3a = 8 + -2

3a = 8 + -2

Combine like terms: 8 + -2 = 6

3a = 6

Divide each side by '3'.

a = 2

Simplifying

a = 2

User Sergey Vedernikov
by
6.0k points